2004
DOI: 10.1097/01.mat.0000129320.57362.db
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation of the Bulbar Conjunctiva in the Goat Implanted with a Total Artificial Heart: Effects of Pulsatile and Nonpulsatile Flow

Abstract: A new system toI observe the microcirculation on the bulbar conjunctiva was developed using a digital high definition microscope to investigate the influence of the flow patterns on the microcirculation in a goat with a total artificial heart (TAH). The undulation pump TAH was implanted into the goat. When the whole body condition became stable, the flow pattern was modulated between the pulsatile and the nonpulsatile mode, and the changes in the microcirculation were observed. When the flow pattern was change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…reported a significant increase of catecholamine level in nonpulsatile systemic circulation accompanied by altered oxygen meta‐bolism (25). Recently, a very important finding was described by Baba et al (2003), who observed the drop of the velocity of erythrocytes in the capillaries of the bulbar conjunctiva and the decreased number of perfused vessels in the conditions of nonpulsatile flow—after the flow was returned to pulsatile, the velocity of erythrocytes and the flow in nonperfused vascular segments recovered to the initial level as well (26,27). This effect of the pulsatile flow is probably related to the enhanced stimulation of the endothelium‐derived nitric oxide release in the terminal microvascular bed (28).…”
Section: Discussionmentioning
confidence: 93%
“…reported a significant increase of catecholamine level in nonpulsatile systemic circulation accompanied by altered oxygen meta‐bolism (25). Recently, a very important finding was described by Baba et al (2003), who observed the drop of the velocity of erythrocytes in the capillaries of the bulbar conjunctiva and the decreased number of perfused vessels in the conditions of nonpulsatile flow—after the flow was returned to pulsatile, the velocity of erythrocytes and the flow in nonperfused vascular segments recovered to the initial level as well (26,27). This effect of the pulsatile flow is probably related to the enhanced stimulation of the endothelium‐derived nitric oxide release in the terminal microvascular bed (28).…”
Section: Discussionmentioning
confidence: 93%
“…The peak activity of these stretch‐sensitive mechanoreceptors located in the viscoelastic walls of the aortic arch and the carotid sinuses has been reported to coincide with the maximum slope of the aortic pressure ( dP/dt, Eq. ) , leading to an increased use of dP/dt to evaluate pulsatile hemodynamic effects : dP/dt=ddtPAomax …”
Section: Methodsmentioning
confidence: 99%
“…Because our blood pump is both a pulsatile type and an occlusive type, we have to consider both aspects during hemolytic testing. From the pulsatile point of view, although there has long been a controversy regarding the clinical benefits of pulsatile and nonpulsatile devices (11)(12)(13)(14)(15), pulsatile flow is important for blood circulation because flow pulsatility can reduce the resistance of peripheral vessels, while blood passes through highresistance areas (16).Therefore, the parameter affecting hemolysis, dP/dt, is crucial in the assessments needed for the development of the pulsatile cardiac device. It is suggested that a high maximum dP/dt results in a high level of hemolysis; the maximum dP/dt of 5000 mm Hg/s is damaging to the blood, while that of 2500 mm Hg/s yields good results in clinical studies (17).…”
mentioning
confidence: 99%